Influence of organisational culture on supply chain resilience: A power and situational strength conceptual perspective - James Whiteside; Samir Dani (Journal of Risk and Financial Management, 2020)
The purpose of this paper is to explore how organisational culture, represented by the competing values framework (CVF), and the relationship mechanisms of situational strength and power influence an organisation's approach to supply chain resilience (SCRES). This is a conceptual paper which uses a multi-theoretical approach to create a framework outlining how organisations which possess different characteristics of culture within the CVF will work to achieve SCRES. Secondary analysis of four case examples as discussed in the supply chain and resilience literature are then used to support the development of propositions from this framework in more detail. The paper suggests that 'flexibility focused' cultures will create weaker situational strengths for supply chain partners when managing disruptions, while 'stability focused' cultures will create stronger situational strengths in the same scenarios. 'Internally focused' cultures may use coercive power with supply chain partners when managing disruptions, while 'externally focused' cultures will prefer non-coercive power in the same scenarios. The four case studies from the literature highlight that each type of culture within the CVF can enable an organisation to achieve SCRES. The practical implications of the findings are that managers should take into consideration how their organisation's culture will influence their relationships with supply chain partners, depending on their application of power and situational strength. However, future research is required to empirically test the propositions.
Keywords: 330; competing values framework; organisational culture; power; situational strength; supply chain resilience